Technical Note: Experimental characterization of the dose deposition in parallel MRI‐linacs at various magnetic field strengths. Issue 11 (9th September 2019) - Begg, Jarrad; Alnaghy, Sarah J.; Causer, Trent; Alharthi, Thahabah; George, Armia; Glaubes, Laura; Dong, Bin; Goozee, Gary; Keall, Paul; Jelen, Urszula; Liney, Gary; Holloway, Lois
Abstract : Purpose: Dose deposition measurements for parallel MRI‐linacs have previously only shown comparisons between 0 T and a single available magnetic field. The Australian MRI‐Linac consists of a magnet coupled with a dual energy linear accelerator and a 120 leaf Multi‐Leaf Collimator with the radiation beam parallel to the magnetic field. Two different magnets, with field strengths of 1 and 1.5 T, were used during prototyping. This work aims to characterize the impact of the magnetic field at 1 and 1.5 T on dose deposition, possible by comparing dosimetry measured at both magnetic field strengths to measurements without the magnetic field. Methods: Dose deposition measurements focused on a comparison of beam quality (TPR20/10 ), PDD, profiles at various depths, surface doses, and field size output factors. Measurements were acquired at 0, 1, and 1.5 T. Beam quality was measured using an ion chamber in solid water at isocenter with appropriate TPR20/10 buildup. PDDs and profiles were acquired via EBT3 film placed in solid water either parallel or perpendicular to the radiation beam. Films at surface were used to determine surface dose. Output factors were measured in solid water using an ion chamber at isocenter with 10 cm solid water buildup. Results: Beam quality was within ±0.5% of the 0 T value for the 1 and 1.5 T magnetic field strengths. PDDs and profiles showed agreement for the three magnetic field strengths at depths beyond 20 mm. Deposited dose increased at shallower depths due to electron focusing. Output factors showed agreement within 1%. Conclusion: Dose deposition at depth for a parallel MRI‐linac was not significantly impacted by either a 1 or 1.5 T magnetic field. PDDs and profiles at shallow depths and surface dose measurements showed significant differences between 0, 1, and 1.5 T due to electron focusing.